Regional Development through Continual Improvement of Higher Education in Latín American Countries Case Study - Rodrigo, Moreno Vallejo Jaime; Gabriel, Fajardo Romo, Frank; Kerchis, Donald E. (European Journal of Social Science Education and Research, 2020)
Aiming to promote the social mission of higher education and their integration in Latin American countries, this research has a qualitative focus and it has the objective to study the normative context and the main theoretical references for the assurance of the quality of higher education for Colombia and Ecuador, examines how the continuous improvement of higher education contributes to regional development; and proposes methodological strategies that contribute to the purpose for the regional development, in a systemic, objective, measurable and achievable in time way, like are the process management and the balanced score card for University Management Strategies and to built a public policy for Latin American Universities.